Prospects for the development of civil aviation in the context of sanctions pressure ("Journal "U". Economy. Management. Finance.", 2024)
This article is devoted to the study of current trends and prospects for the development of civil aviation in conditions of increased sanctions pressure. In recent years, Russian civil aviation has faced numerous challenges related to restrictions on the import of aviation technologies, spare parts and components, as well as a Журнал «У». Экономика. Управление. Финансы. 3/2024  www.portal-u.ru 101 reduction in international air traffic. The conducted research shows that overcoming current barriers requires both intensive government intervention and active partnership between the public and private sectors.
Keywords: civil aviation; sanctions; the Russian Federation; aviation development; government intervention; sanctions pressure